PERWALIAN PENGURUSAN HARTA WARISAN ANAK DI BAWAH UMUR MENURUT HUKUM PERDATA (STUDI KASUS DI KELURAHAN KANDIS KOTA KECAMATAN SIMPANG BELUTU KABUPATEN SIAK) - Kamal, Alisa; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
If one of the parents dies, the guardianship of children who are immature by law is held by the parent who lives the longest, if one of the husband or wife dies, the husband or wife who lives the longest along with their offspring who are heirs. from the inheritance. If the minor is possessed by the inheritance of the inheritor, the parent who lives the longest is the guardian of the child regarding the care of the child and his assets. In this case related to guardianship issues that occur in Kelurahan Kandis Kota. The purpose of writing this thesis is, first, to find out whether guardianship based on Article 345 KHUPerdata in Kandis Kota Kelurahan, Second, factors that cause guardian neglect in the management of the inheritance of minors in Kandis Kota Kelurahan.This type of research can be classified as sociological research, because in this study the authors directly conduct research at the location or place under study. This research was conducted in the Kelurahan Kandis Kota, while the population and sample were all parties related to the problems examined in this study, data sources, used, primary data, secondary data, and tertiary data, data collection techniques in this study with observation , interviews and literature studies.From the results of the research there are a number of things that can be concluded, first, the determination of guardianship based on Article 345 KHUPerdata that if one of the two parents dies, the parents who live the longest automatically become the guardian of the law for their children while what happens in this problem is the living parent the longest i.e. the mother does not become the guardian of her children. Second, the factors that cause guardian neglect in the management of the inheritance of minors based on the problems studied are due to conflicts in the family between birth mother and uncle and aunt so that the children's rights are ignored and the lack of responsibility of the guardian himself against the inheritance of minors.Keywords: Guardianship, Minors, Responsibility